Melanoma patterns of distant relapse: a study of 108 cases from a South Brazilian center - Rovere,Rodrigo Kraft (2016)
Abstract Background: The incidence of cutaneous melanoma has increased over the last decades. Recurrences occur most frequently within the first 2-3 years after diagnosis but patients carry a lifelong risk of relapse. Nevertheless, there is no consensus in the literature on what screening tests patients should undergo. Objectives: To evaluate the most common melanoma metastasis sites among a South Brazilian population from a city with one of the highest melanoma rates, and establish the best screening method for these patients. Methods: A cross-sectional retrospective study of 108 consecutive melanoma patients followed up at a center from 2009 to 2013. Data were collected on demographic and tumoral characteristics, as well as the site of the first diagnosed metastasis. Results: Patients were divided into 3 groups for analytical purposes: Non-visceral metastases (48% of patients), visceral metastasis (39%) and brain metastasis (13%). We tried to correlate age, gender, mean Breslow thickness, mitosis and death rates with the aforementioned groups but none showed any statistically significant association. Conclusion: Melanoma patients must be monitored to detect early relapse and subsequent effective treatment but the best follow-up strategy remains to be established.